The impact of changed treatment patterns in multiple myeloma on health‐care utilisation and costs, myeloma complications, and survival: A population‐based comparison between two time periods in Denmark. (12th April 2021) - Hannig, Louise Hur; Nielsen, Lene Kongsgaard; Ibsen, Rikke; Arnheim‐Dahlström, Lisen; Kjellberg, Jakob; Abildgaard, Niels
Abstract: Objectives: To evaluate health‐care utilisation and costs, myeloma complications and survival in Danish patients with multiple myeloma (MM) before and after implementation of new early‐line treatments in 2009. Methods: Based on data from the Danish National Health Registers, 3518 patients diagnosed with MM during 2002‐2005 or 2010‐2013 and randomly matched control individuals were identified, and health‐care utilisation and costs were estimated. Results: Health‐care utilisation showed a marked shift from inpatient admissions towards outpatient visits. From early to late period, the mean annual number of outpatient visits increased by 22% and 28% in patients <65 years and ≥65 years, respectively. Additionally, the mean annual outpatient service costs increased correspondingly from 17 001€ to 23 643€ in younger patients and from 11 317€ to 16 144€ in the elderly. Increasing outpatient costs were outbalanced by lower inpatient admission costs and the adjusted total mean annual costs decreased in younger patients, probably partly due to fewer myeloma complications. The five‐year survival rates increased markedly in both younger (HR = 0.51) and elderly (HR = 0.69) patients. Conclusion: Despite the introduction of new expensive early‐line MM treatments in 2009, health‐care costs remained stable due to a shift in health‐care utilisation towards outpatient clinic care and fewer complications.